Symptoms and self-care strategies during and six months after radiotherapy for prostate cancer – Scoping the perspectives of patients, professionals and literature. (April 2016) - Blomberg, Karin; Wengström, Yvonne; Sundberg, Kay; Browall, Maria; Isaksson, Ann-Kristin; Nyman, Maria Hälleberg; Langius-Eklöf, Ann
Abstract: Purpose: Under-diagnosed and uncontrolled symptoms in patients with prostate cancer during radiotherapy can have a negative impact on the individual's quality of life. An opportunity for patients to report their symptoms systematically, communicate these symptoms to cancer nurses and to receive self-care advice via an application in an Information and Communication Technology-platform could overcome this risk. The content in the application must precisely capture symptoms that are significant to both patients and health care professionals. Therefore, the aim of the study was to map and describe symptoms and self-care strategies identified by patients with prostate cancer undergoing radiotherapy, by health care professionals caring for these patients, and in the literature. Methods: The study combines data from interviews with patients (n = 8) and health care professionals (n = 10) and a scoping review of the literature (n = 26) focusing on the period during and up to 6 months after radiotherapy. Results: There was a concordance between the patients, health care professionals, and the literature on symptoms during and after radiotherapy. Urinary symptoms, bowel problems, pain, sexual problems, fatigue, anxiety, depression, cognitive impairment and irregular symptoms were commonly described during the initial treatment period. Self-care strategies were rarely described in all three of the sources. Conclusions: The results show which symptoms to regularly assess using an Information and Communication Technology-platform for patients with newly-diagnosed prostate cancer during radiotherapy. The next step is to evaluate the efficacy of using the platform and the accuracy of the selected symptoms and self-care advice included in a smartphone application. Highlights: A concordance existed in view of symptoms. Urinary and bowel symptoms were the most common symptoms. Self-care strategies were rarely described. Gives an indication of symptoms to regularly collect in an ICT-platform.